Advanced imaging tools for evaluating cardiac morphological and functional impairment in hypertensive disease. Issue 1 (January 2022) - Lembo, Maria; Manzi, Maria Virginia; Mancusi, Costantino; Morisco, Carmine; Rao, Maria Assunta Elena; Cuocolo, Alberto; Izzo, Raffaele; Trimarco, Bruno
Abstract : N/A: Arterial hypertension represents a systemic burden, and it is responsible of various morphological, functional and tissue modifications affecting the heart and the cardiovascular system. Advanced imaging techniques, such as speckle tracking and three-dimensional echocardiography, cardiac magnetic resonance, computed tomography and PET-computed tomography, are able to identify cardiovascular injury at different stages of arterial hypertension, from subclinical alterations and overt organ damage to possible complications related to pressure overload, thus giving a precious contribution for guiding timely and appropriate management and therapy, in order to improve diagnostic accuracy and prevent disease progression. The present review focuses on the peculiarity of different advanced imaging tools to provide information about different and multiple morphological and functional aspects involved in hypertensive cardiovascular injury. This evaluation emphasizes the usefulness of the emerging multiimaging approach for a comprehensive overview of arterial hypertension induced cardiovascular damage.